Calcitonin Levels in Thyroid Disease Are Not Affected by Autoimmune Thyroiditis or Differentiated Thyroid Carcinoma. Issue 4 (12th July 2021) - Maino, Fabio; Dalmiglio, Cristina; Benenati, Nicoletta; Campanile, Michele; Pilli, Tania; Forleo, Raffaella; Brilli, Lucia; Ciuoli, Cristina; Cantara, Silvia; Capezzone, Marco; Cartocci, Alessandra; Pacini, Furio; et al.
Abstract : Introduction: Association between hypercalcitoninemia and pathological conditions such as autoimmune thyroiditis (AIT) or differentiated thyroid carcinoma (DTC) has been addressed, with conflicting results. We evaluated the prevalence and the clinical relevance of elevated basal serum calcitonin (CT) levels in non-neoplastic (nodular goiter [NG] and AIT) and neoplastic thyroid diseases (DTC). Methods: We retrospectively evaluated 3, 250 consecutive patients with thyroid nodular disease who underwent fine-needle aspiration cytology with adequate sample. After exclusion of medullary thyroid cancer (MTC) patients were divided according to the presence/absence of thyroid autoimmunity into NG or nodular autoimmune thyroiditis (N-AIT) and, according to cytological results, in benign or suspicious/malignant nodules. Results: One hundred ninety-seven/3, 250 patients (6.0%) showed CT level >10 pg/mL. In 11/3, 250 (0.3%) cases, a final histological diagnosis of MTC was made, while the remaining 186/3, 250 patients (5.7%) had non-MTC-related hypercalcitoninemia (CT > 10 pg/mL). According to cytological diagnosis, the rate of hypercalcitoninemia was similar in class II and class V–VI groups (5.4 vs. 6.9%, p = 0.4). The occurrence of hypercalcitoninemia was significantly higher in patients with NG (166/2, 634 [6.3%]) than in patients with N-AIT (20/605 [3.3%]) ( p = 0.004). However, after matching by sex, no difference was found between the 2 groups (NG and N-AIT). These results were confirmed in 598 patients submitted to surgery. Conclusions: AIT and DTC seem not to affect serum CT levels in patients with thyroid nodules. Therefore, hypercalcitoninemia, in these patients, should be submitted to the same diagnostic workup than patients without AIT or DTC.